INTERNALISASI NILAI-NILAI ISLAM DALAM PENDIDIKAN LINGKUNGAN UNTUK MEMBANGUN KESADARAN EKOLOGIS PESERTA DIDIK - Ryan Radjendra; Silpa; Chairul Amriyah; Junaidah; Ihsan Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the process of internalizing Islamic values in environmental education as an effort to develop students’ ecological awareness. The research employs a library research method with a qualitative-descriptive approach through a review of relevant literature, Qur’anic interpretations, and previous studies. The findings indicate that Islamic values such as tauhid (oneness of God), khalifah (human stewardship), amanah (responsibility), and adl (justice) have strong relevance to environmental education. The internalization of these values fosters environmentally responsible behavior rooted in Islamic spirituality and morality. Islamic education that emphasizes ecological values can enhance students’ awareness to protect, preserve, and utilize nature wisely according to the principles of sustainability. Therefore, environmental education based on Islamic values not only builds ecological consciousness but also strengthens students’ religious character and social responsibility as God’s stewards on earth. Keywords: Islamic values, environmental education, ecological awareness, internalization, human responsibility.